4-Dimethylaminopyridine-catalyzed [3 + 3] spiroannulation reactions of isatin-derived Morita-Baylis-Hillman carbonates with indoline-2-thiones. (20th July 2022) - Geng, Congcong; Wei, Xingfu; Xu, Yongqiang; Liu, Jianhui; Peng, Lizeng; Wang, Baomin
Graphical abstract: DMAP-catalyzed diastereoselective [3 + 3] spiroannulations of isatin-derived Morita-Baylis-Hillman carbonates with indoline-2-thiones were achieved. A series of bisindole-annulated thiopyran frameworks were synthesized in good yields with good diastereoselectivities. The strategy developed in this paper offered a novel way for the synthesis of valuable indole-annulated sulfur heterocycle derivatives which might be beneficial in organic synthesis and medicinal chemistry. Highlights: A novel way for the synthesis of valuable indole-annulated sulfur heterocycle derivatives. Bisindole-annulated thiopyran derivatives were synthetized under mild conditions. DMAP-catalyzed diastereoselective [3 + 3] spiroannulations of isatin-derived Morita-Baylis-Hillman carbonates with indoline-2-thiones. Abstract: DMAP-catalyzed diastereoselective [3 + 3] spiroannulations of isatin-derived Morita-Baylis-Hillman carbonates with indoline-2-thiones were achieved. A series of bisindole-annulated thiopyran frameworks were synthesized in good yields with good diastereoselectivities. The strategy developed in this paper offered a novel way for the synthesis of valuable indole-annulated sulfur heterocycle derivatives which might be beneficial in organic synthesis and medicinal chemistry.